The role of stock exchange indices in the economy: the adaptation of international experience in the republic of kazakhstan (Journal of Economic Research & Business Administration, 2016)
The article dedicated to the role of stock exchange indices in the economy, particularly to the analysis of the index KASE shares, which is based on international experience. To conduct the analysis, fundamental functions of stock indices on the example of global stock indices were considered, as well as methodology of their calculation that are widely used in the world practice, followed by further adaptation of the experience in Kazakhstan. The conducted study revealed peculiarities of KASE stock index functioning, as well as future prospects of its development.
Keywords: stock index; stock index KASE; the method of simple arithmetic average; the method of geometric average; the method of arithmetic average weighted; Dow Jones Average; S&P 500; FT30; a representative list of KASE shares index.